Вимірювання координат радіомаяка безпілотного літального апарата - Чигінь, В. І.; Chyhin, Vasyl (Видавництво Львівської політехніки, 2019)
Розроблено і випробувано експериментальну систему для вимірювання параметрів траєкторії польоту власного об’єкта-радіомаяка, зокрема, у складі безпілотного літального апарата (БПЛА). Робота основана на вимірюванні різниць фаз радіохвиль від радіомаяка, які надходять до рознесених антен. Як наземну приймальну пасивну радіо- систему використано скеровані антени типу п’ятиелементного квадрата. Вимірювач різниці фаз створено на основі мікросхеми AD8302, яка працює у діапазоні частот до 2,7 ГГц і забезпечує нелінійність вимірювання різниці фаз не більше ніж 1 град у діапазоні від 30 до 140 град. Експериментальна система дає змогу швидко переміщати генератор радіохвилі, встановлений у БПЛА “Фантом 3”, у довільному напрямку щодо напрямку приймальних антен. Політ БПЛА у просторі, віддаленому від приземної поверхні, забезпечив різке зниження впливу навколишніх радіошумів. Отримані вперше за допомогою АЦП і спеціальної програми експериментальні залежності різниці фаз від часу польоту БПЛА задовільно якісно і кількісно описують теоретичну криву залежності різниці фаз радіохвилі з частотою 433 МГц від віддалі до антен.

An experimental system for measuring the parameters of the flight trajectory of its own object-radio beacon, in particular, in the unmanned aerial vehicle (UAV) is developed and tested. Passive radio-location system is used. The differencephase, difference-time and difference-frequency methods are compared. The first one provides the sufficient precision, not more than 1 deg. in the range of 30 to 140 deg. The phase measuring device is based on chip AD8302, operating at the frequency range up to 2.7 GHz. The fulfilled assessment has underlined the ability to measure the trajectory of objects-radio beacons in range of several kilometers. A set of measurements has performed under different conditions in near ground and free atmosphere. UAV flight in air, far from the surface of ground, provided a sharp decrease of an influence of surrounding radio noises. The deviation of the UAV flight line from the vertical axis of the antenna is possible due to the deflection of the UAV from this axis at altitudes of 100 or more meters due to strong winds at these altitudes and due to the possible deviation of the antenna axis from the vertical. Obtained experimental dependences of the phase difference on flight time of the UAV are satisfactory and describe the dependence of the phase difference of radio waves at 433 MHz. The narrow RF filter eliminates the impact of most RF sources such as radio broadcast stations, industrial noise. Geometrical shortcomings can be avoided by inclusion of photodetectors and horizontally leveling of antennas. The obtained results envisage the system’s suitability for localization of objects with radio beacons onboard in a range of several kilometers as well as the possibility of the proposed methodology application for measuring the coordinates of unknown UAVs and ballistic objects.
Measurement of coordinates of unmanned aerial vehicle radio beacon
Keywords: безпілотний літальний апарат; радіомаяк; пасивна радіолокаційна система; різниця фаз; координати; Unmanned aerial vehicle; Radio beacon; Passive radar system; Phase difference; Coordinates